Solid-state mechanochemical activation of clay minerals and soluble phosphate mixtures to obtain slow-release fertilizers. (2nd January 2018) - Borges, Roger; Brunatto, Silvio F.; Leitão, Alexandre A.; De Carvalho, Gustavo S. G.; Wypych, Fernando
Abstract: This work describes the development of potential multi-element slow-release fertilizers obtained by mechanochemical activation of mixtures of kaolinite and ammonium or potassium monohydrogen phosphates. Preliminary results of talc amorphization have also been included. The methodology consists of milling the materials in a high-energy ball mill, where the influence of rotation and time of milling were investigated. The samples were characterized by XRD, FTIR, TGA/DTA, SEM and MAS-NMR. The experimental results explain the slow-release behaviour of the amorphous nanostructured materials in aqueous suspensions, especially the MASNMR spectra, which showed the changes in the chemical environment of the elements analysed. The materials displayed slow-release behaviour for phosphates probably because the aluminium ions in the mineral structure interact more thoroughly with phosphate than potassium or ammonium. Nevertheless, in general, all of the nutrients were released slowly.